Resilience of student youth in Russia under uncertainty - A. V. Makhnach; A. I. Laktionova; Yu. V. Postylyakova (Образование и наука)
Introduction. The article analyses resilience of university students. The high degree of uncertainty of the present and future, associated with the characteristics of the life stage of graduate students, is complicated by the fact that this age period is associated with crises in choosing a profession. It is shown that the relationship between youth resilience and the development of their life trajectory has been little studied. The relevance of such studies is high and has theoretical and practical significance. Research hypothesis: the level of students’  resilience is associated with an optimistic/pessimistic vision of their professional future in Russia, self-identification, reflecting belonging to a country, region, city, migration/emigration intentions.Aim. The study aims to analyse the relationship of youth resilience with their attitude to the prospects of their future profession, migration/emigration intentions, and social identity.Methodology, methods and techniques. The methodological framework of research is based on the systematic approach that offers system-wide ideas about the structural and functional structure of the space of research objects; the theory of ecological systems by U. Bronfenbrenner, which allows to identify significant relationships between the indicators of youth resilience in interaction with the outside world. Students’ resilience was assessed by the 28-item Child and Youth Resilience Measure (Child and Youth Resilience Measure-28), which allows scoring three indicators of resilience: “Individual resources”; “Family support”; “Context”. The calculation of the integral resilience score is provided. The authors developed the questionnaire to study the social identity of young people, their attitude to the prospects of their future profession and migration/emigration intentions. The study involved university senior students, MA level students (N = 993, average age M = 21.49, SD = 2.274).Results. 1. In resilience of students, individual resources are leading; family resources and score of general resilience are moderate; students give a low rating to contextual resources. 2. Students with high resilience are more optimistic about the opportunities for professional growth and a decent life in Russia, in contrast to students with low resilience. 3. Social identity differs between high and low resilience groups. Higher indicators of self-identification as Russians are demonstrated by students with high resilience, they also have less pronounced cosmopolitanism and emigration plans. 4. A low assessment of the physical and psychological support of family, friends, and dissatisfaction with home/family/friends is noted among respondents with low resilience, which also demonstrates a pessimistic vision of the future in Russia, higher emigration intentions, and lower indicators of self-identification as a Russian citizen. 5. Data from the study of the general sample show regional differences in the migration/ emigration plans of young people.Scientific novelty. The empirical possibilities of the systems approach and the theory of ecological systems by U. Bronfenbrenner to the study of student youth resilience have been tested. The relationships between young people resilience and their attitude to the prospects of the profession, migration/emigration intentions, and social identity are revealed. The targets of influence on increasing students’ resilience during their studies at the university are determined. Practical significance. The results of the present study can be used for individual support of students and in the preparation of university curricula.